2013
DOI: 10.1158/2159-8290.cd-13-0117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Epigenetic Chemosensitization Therapy of Diffuse Large B-Cell Lymphoma

Abstract: Although aberrant DNA methylation patterning is a hallmark of cancer, the relevance of targeting DNA methyltransferases (DNMT) remains unclear for most tumors. In diffuse large B-cell lymphoma (DLBCL) we observed that chemo-resistance is associated with aberrant DNA methylation programming. Prolonged exposure to low-dose DNMT inhibitors (DNMTIs) reprogrammed chemo-resistant cells to become doxorubicin sensitive without major toxicity in vivo. Nine genes were recurrently hypermethylated in chemo-resistant DLBCL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 63 publications
10
173
0
Order By: Relevance
“…In particular, we suggested that the absence of non-genetic instability can result in the stabilization of the DTP phenotype in the surviving population, so that DTEPs do not emerge, or even in extinction. This is a key result since it supports the idea that epigenetic therapy may be a promising therapeutic strategy in the war against cancer [16][17][18]. Another important prediction of our models is that the transient dominance of DTPs is strictly related to the use of high doses of cytotoxic drugs.…”
Section: Resultssupporting
confidence: 76%
“…In particular, we suggested that the absence of non-genetic instability can result in the stabilization of the DTP phenotype in the surviving population, so that DTEPs do not emerge, or even in extinction. This is a key result since it supports the idea that epigenetic therapy may be a promising therapeutic strategy in the war against cancer [16][17][18]. Another important prediction of our models is that the transient dominance of DTPs is strictly related to the use of high doses of cytotoxic drugs.…”
Section: Resultssupporting
confidence: 76%
“…The DMRs can also be used to predict response of patients with chronic myelomonocytic leukaemia to DNMTi [109]. Hypermethylation and silencing of SMAD1 was useful as a predictive biomarker for chemotherapy resistance in patients with high-risk diffuse large B-cell lymphoma (DLBCL) [110]. SMAD1 silencing also showed contribution to chemotherapy resistance that can be reversed by DNMTis in patients [110].…”
Section: Dna Methylation Biomarkers Treatment and Monitoring Of Dismentioning
confidence: 99%
“…Hypermethylation and silencing of SMAD1 was useful as a predictive biomarker for chemotherapy resistance in patients with high-risk diffuse large B-cell lymphoma (DLBCL) [110]. SMAD1 silencing also showed contribution to chemotherapy resistance that can be reversed by DNMTis in patients [110]. Results were favourable for the use of DNMTi in patients diagnosed with high-risk DLBCL, in combination with decitabine before rituximab in combination of cyclophosphamide, doxorubine, vincristine and prednisone chemo-immunotherapy.…”
Section: Dna Methylation Biomarkers Treatment and Monitoring Of Dismentioning
confidence: 99%
“…Indeed DNA methylation has a critical role in genome integrity by repressing transcription at repeated sequences, including highly mutagenic retrotransposon elements. When located in promoters, CpG island DNA hypermethylation is also associated with a repressed chromatin and thus transcription inhibition (Iguchi-Ariga and Schaffner, 1989;Watt and Molloy, 1988;Prendergast and Ziff, 1991;Clozel et al, 2013). Genes located downstream are silenced although their genomic sequence is intact.…”
Section: Iii-what Is the Role Of Dna Methylation?mentioning
confidence: 99%
“…By targeting DNA methylation, cells are reprogrammed; reexpression of TSG can induce cell arrest, differentiation and death, but also sensitivity to apoptosis, immuno-response and drug treatment. An example is the reversal of the resistance to doxorubicine in diffuse large B-cell lymphoma (DLBL) by low-doses of DNMT inhibitors (Clozel et al, 2013). It exists two classes of DNMT inhibitors (DNMTi): the nucleoside analogues that are incorporated into nucleic acids and form a covalent complex with the enzyme, and the non-nucleoside inhibitors that present different mechanisms of inhibition.…”
Section: Vi-present and The Future Of Dna Methylation Cancer Therapymentioning
confidence: 99%